A Histochemical Method for the Demonstration of Diphosphopyridine Nucleotide Diaphorase - Nachlas, Marvin M. (The Rockefeller University Press, 1958)
The present investigation concerning the histochemical demonstration of DPN diaphorase follows the development of a new reagent, Nitro-BT, which has already been used successfully for the cytochemical localization of the succinic dehydrogenase system. The most consistently favorable results were obtained with the lactate-lactic dehydrogenase system buffered at pH 7.4. Using sections of rat kidney and stomach, it was found that the intensity of stain was optimal after 15 minutes incubation at 37°C., conducted aerobically. By appropriate variations in the substrate mixture it was possible to selectively demonstrate the histochemical distribution of certain DPN-linked dehydrogenases in addition to DPN diaphorase. This was made possible by the special distribution of some of these dehydrogenases which distinguished them from one another. Of the dehydrogenases studied the distribution pattern of β-hydroxybutyric dehydrogenase was the most singular. In the gastric mucosa β-hydroxybutyric dehydrogenase was restricted to the cells of the mucous lining epithelium and the gland necks; and in the kidney the enzyme was limited to the cells of the proximal convoluted tubule and thick limbs of Henle's loop. In contrast, lactic dehydrogenase like DPN diaphorase was demonstrable in almost all cytologic elements of both the stomach and the kidney.